Bioefficacy of Emamectin Benzoate Against Helicoverpa armigera Hubner and its Natural Enemies on chickpea (Cicer arietinum) Crop - Chaukikar, Kailash; Bhowmick, A. K.; Das, S. B.; Marabi, R. S.; Singh Tomar, Vivek (International Journal of Bio-resource and Stress Management, 2017)
An experiment was carried out to investigate the bioefficacy of Emamectin benzoate against the larvae of Helicoverpa armigera and its natural enemies on chickpeaat Breeding Seed Production Farm, JNKVV, Jabalpur, Madhya Pradesh, India, consecutively for two years during rabi season 2009 and 2010. The trial was laid out in Randomized Block Design with seven treatments and three replications. The pooled data of two years indicated that Emamectin benzoate 5% WG @ 9.4 and 8.1 g a.i. ha-1 were found to be most effective dose in reducing the H. armigera larval population and pod damage (1.28% and 1.29%, respectively) followed by Emamectin benzoate 5% WG @ 6.9 and 5.6 g a.i. ha-1 with 1.33 and 3.72% pod damage, respectively. The standard treatments of Chlorpyrifos 20% EC @ 500 g a.i. ha-1 and Ethion 50% EC @ 500 g a.i. ha-1 recorded 7.40% and 7.72% pod damage, respectively as compared to control plot (10.89% pod damage). All the treatments of Emamectin benzoate 5% WG did not show any adverse effects against Lady bird beetle and Chrysopa and no phytotoxic effects was observed on the chickpea crop. Seed yield was maximum (2260 kg ha-1) with the highest dose of Emamectin benzoate 5% WG @ 9.4 g a.i ha-1 followed by Emamectin benzoate 5% WG @ 8.1 and 6.9 g a.i ha-1, respectively.